2021
DOI: 10.1021/acsami.1c03859
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Enhancement of MOF/Polymer Adhesion in Mixed-Matrix Membranes via Polymer Functionalization

Abstract: MOF-based mixed-matrix membranes (MMMs) prepared using standard routes often exhibit poor adhesion between polymers and MOFs. Herein, we report an unprecedented systematic exploration on polymer functionalization as the key to achieving defect-free MMMs. As a case study, we explored computationally MMMs based on the combination of the prototypical UiO-66­(Zr) MOF with polymer of intrinsic porosity-1 (PIM-1) functionalized with various groups including amidoxime, tetrazole, and N-((2-ethanolamino)­ethyl)­carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Not all polymer-MOF combinations are suitable for forming MMMs, as MOF particles often fail to combine well with the polymer matrix and can suffer from particle aggregation that disrupt the function and mechanical strength of the resulting MMM. [26][27][28] The uniform and aggregation-free dispersion of MOF particles in a polymer matrix play an essential role in improving the mechanical strength of composites. 29 The fabrication of polymeric composites using in situ polymerization may improve the dispersion homogeneity and distribution of the MOF fillers in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Not all polymer-MOF combinations are suitable for forming MMMs, as MOF particles often fail to combine well with the polymer matrix and can suffer from particle aggregation that disrupt the function and mechanical strength of the resulting MMM. [26][27][28] The uniform and aggregation-free dispersion of MOF particles in a polymer matrix play an essential role in improving the mechanical strength of composites. 29 The fabrication of polymeric composites using in situ polymerization may improve the dispersion homogeneity and distribution of the MOF fillers in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…23. Carja et al 167 prepared UiO-66(Zr) and PIM-1 modified with different groups (amidoxime, tetrazole, and N -((2-ethanolamino)ethyl)carboxamide) into MMMs, and found that functionalization of polymers was the key to achieving defect-free MMMs. Compared with raw PIM-1, the CO 2 permeability of the amine-modified UiO-66(Zr)/PIM-1MMMs increased by 30% to 1380.4 barrer at 308 K, 1.93 bar.…”
Section: Application Of Mofs For Co2 Capturementioning
confidence: 99%
“…Mixed-matrix membranes (MMMs) based on the incorporation of metal–organic framework (MOF) micro- or nanoparticles as fillers into polymer matrices are promising materials for separation technologies, sensing, and optoelectronic devices. MMMs offer the ability to integrate the advantages of MOFs and polymers into one system. Due to the modular and concise structural features of both MOFs and polymers, MMMs offer tunable structure-related properties, which have been extensively investigated in separation science. However, the interfacial investigations of their optical properties are relatively limited.…”
Section: Introductionmentioning
confidence: 99%